Cornflake ikan teri nasi substitusi tepung kacang koro pedang (canavalia ensiformis) ditinjau dari segi kesukaan, karakteristik fisik, dan kandungan gizi - Afita Rachim; Siti Fathonah (Jurnal Sains Boga, 2026)
Stunting, as a child development problem, can be addressed by providing protein-rich foods. One well-known example is cornflake. Cornflake anchovy substitute for jackbean flour is an innovation and modification that was researched with the aim of determining the level of public preference, the physical characteristics, and the nutritional content of peroxide value, protein, and water content. The research method used was a completely randomized design, The data analysis technique used was a preference test using the Kruskal-Wallis test followed by the Mann-Whitney test, and a physical characteristic test using colorimeter and penetrometer, and peroxide value tests, protein content test, and water content test. The results of the study show that cornflake anchovy substitute for jackbean flour STKP 0%, STKP 5%, STKP 15%, and STKP 25% have significant difference with p value = 0.000. STKP 15% is the preffered one with a nutritional content of peroxide value, protein, and water content of 2.05 mEq O2/kg, 14.62%, and 9.65%, respectively. STKP 15% was further studied in meeting protein needs snack and the results obtained show that all categories have their needs met with a value above 10% in 30g. Based on the results of this study, it can be concluded that cornflake anchovies substituted for jackbean flour can be a protein-rich snack. It is recommended that further research be conducted to evaluate the agar formula cornflake anchovy substitute for jackbean flour can meet SNI requirements.